2019
DOI: 10.1590/1806-9061-2018-0754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Essential Oils on Vitamin C, Malondialdehyde and Some Biochemical Parameters of Rats*

Abstract: The aim of this study was to determine the LD 30 values of the essential oils of Origanum minutiflorum He Schwarz-PH Davis (OM) and Juniperus excelca by Bieb.subsp. Excel (JE) in vivo investigation on the effects of malondialdehyde (MDA), vitamin C and some biochemical parameters. In this, study the essential oils of OM and JE plants were used. LD 50 values of the essential oils were determined by using rats. OM (n=10), JE (n=10), carvacrol (n=10) which dissolve in olive oil were used as experimental group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…In this study, both the AST and ALT levels in the corn group and the AST / ALT ratio of less than 2 indicate that the negative effects of corn gluten on the liver were lower than wheat gluten and the low GGT level in the corn group supported this (De Bruyn and Graviss, 2001;Giannini et al, 2003). Similar to the results obtained in this study, Göze et al (2019) in their study of rats in animals with liver damage, serum AST, ALT and GGT levels have been reported to increase and AST / ALT ratio is over 2.…”
Section: Resultssupporting
confidence: 88%
“…In this study, both the AST and ALT levels in the corn group and the AST / ALT ratio of less than 2 indicate that the negative effects of corn gluten on the liver were lower than wheat gluten and the low GGT level in the corn group supported this (De Bruyn and Graviss, 2001;Giannini et al, 2003). Similar to the results obtained in this study, Göze et al (2019) in their study of rats in animals with liver damage, serum AST, ALT and GGT levels have been reported to increase and AST / ALT ratio is over 2.…”
Section: Resultssupporting
confidence: 88%
“…Statistical significance was defined as a (P value < 0.05). These outcomes hold predictive implications for the broader finding [17].…”
Section: Statistical Investigationmentioning
confidence: 73%